Tribology of miniature systems - Rymuza, Zygmunt, 1944- (Tribology series, 1989)
The tribology of miniature systems is quite different from the tribology of large machinery. This is the first publication to cover on an academic level both the basic concepts of the tribology of miniature systems and some areas of its practical application. A comprehensive survey is given on the specific problems encountered in this field, providing a volume that will be useful in solving professional engineering problems in the fast growing field of precision engineering and microtechnology. The suitability of various materials and lubricants for the tribological systems in miniature mechanisms is discussed. The tribological properties and the friction and wear properties which occur in such systems are analysed. Specific lubrication problems are examined in detail; in particular, the use of special tribological coatings to solve many difficult lubrication problems and to obtain high wear resistance of the rubbing elements is considered. The special investigation techniques used to characterize miniature tribological systems and their elements (e.g. lubricants) are reviewed. The tribological aspects of many of the most common assemblies found in miniature mechanism and electromechanism design are analysed and some practical suggestions are put forward for the rational design of such systems. Also special tribological problems such as those met in computer technology, bioengineering, etc. are presented. The book is intended for tribologists (both seasoned researchers and newcomers) studying the problems of this specific branch of tribology and also for practising engineers active in the design, manufacture and exploitation of various miniature systems.